About robust hyperstability and dissipativity of linear time-invariant dynamic systems subject to hyperstable controllers and unstructured delayed state and output disturbances. Issue 1 (1st January 2018) - De la Sen, M.
Abstract: This paper considers the robust asymptotic closed-loop hyperstability of a nominal time-invariant plant with an associate strongly positive real transfer function subject to unstructured disturbances in the sate and output. Such disturbances are characterized by upper-bounding growing laws of the state and control. It is assumed that the controller is any member within a class which satisfies a Popov´s type integral inequality. The continuous-time nonlinear and perhaps time-varying feedback controllers belong to a certain class which satisfies a discrete-type Popov´s inequality. The robust closed-loop hyperstability property is proved under certain explicit conditions of smallness of the coefficients of the upper-bounding functions of the norms of the unstructured disturbances related to the absolute stability abscissa of the modelled part of the nominal feed-forward transfer function.